Peculiar Mode of Expression: Judge Doe’s Use of the Distinction Between Law and Fact - John Phillip Reid (Washington University Law Quarterly, 1963)
Although Chief Justice Doe probably never constructed a system of general principles on the higher levels of jurisprudence, there have been very few judges who have had a firmer grasp on the workings of the common law or have known better how to manipulate its doctrines and rules. He had an intuition for developing its strengths and seizing upon its weaknesses; to make those challenging his views debate issues along lines he set down. As Dean Pound pointed out, Doe combined “sound legal instincts” with a “thorough knowledge of traditional legal methods,” and this permitted him, even when advancing radical ideas, to force opponents on the defensive. By giving close study to pedestrian matters which few judges of his intellectual curiosity would have detained, he not only learned to master basic common-law tools such as the distinction between law and fact, but became convinced that the unity of legal science could be effected more by procedural and evidentiary rules than by elusive, abstract principles of jurisprudence.
Keywords: Biography; Charles Cogswell Doe